Keep Me In, Coach: The Short- and Long-Term Effects of Targeted Academic Coaching - Serena Canaan; Stefanie Fischer; Pierre Mouganie; Geoffrey C. Schnorr (Institute of Labor Economics (IZA), 2022)
To boost college graduation rates, policymakers often advocate for academic supports such as coaching or mentoring. Proactive and intensive coaching interventions are effective, but are costly and difficult to scale. We evaluate a relatively lower-cost group coaching program targeted at first-year college students placed on academic probation. Participants attend a workshop where coaches aim to normalize failure and improve self-confidence. Coaches also facilitate a process whereby participants reflect on their academic difficulties, devise solutions to address their challenges, and create an action plan. Participants then hold a one-time follow-up meeting with their coach or visit a campus resource. Using a difference-in-discontinuity design, we show that the program raises students' first-year GPA by 14.6% of a standard deviation, and decreases the probability of first-year dropout by 8.5 percentage points. Effects are concentrated among lower-income students who also experience a significant increase in the probability of graduating. Finally, using administrative data we provide the first evidence that coaching/mentoring may have substantial long-run effects as we document significant gains in lower-income students' earnings 7–9 years following entry to the university. Our findings indicate that targeted, group coaching can be an effective way to improve marginal students' academic and early career outcomes.
Keywords: I23; I24; J16; 330; college graduation; mentoring; college advising; academic coaching